Financial disclosure of Malaysian local authorities: an institutional theoretical perspective - Anak Teruki, Neilson (Academia Industry Networks, 2020)
The role of organizational and environmental factors in explaining financial disclosure has thus far not been adequately addressed. Neither has there been an attempt to use field studies to explain the financial disclosure practices in the organization. There has thus been a consistent failure to relate the effect of institutional and social aspects and the quality of disclosures in organizations’ financial statements. Consequently, there is a need to carry a study to explain the disclosure practices and management in the public sector by incorporating organizational, social and environmental factors. These factors are expected to have an influence on the manager’s decision to disclose information. This study seeks to investigate the range of issues considered when making financial disclosure decisions, the role of auditor(s) and other external parties in the disclosure process, and the influence of external disclosure rules on disclosure decisions. The concept of isomorphism is examined under the institutional theory lens and used to explain the influences on the disclosure practices in MLAs. The study adopts a case study approach using semi-structured interviews and internal documents. The fieldwork consists of interviews with 33 people who worked at different levels, held different positions and were from a variety of backgrounds of five MLAs together with document analysis. The study concluded that there is an existence of coercive, normative and mimetic isomorphism in MLAs disclosure practices. The isomorphism comes from mimetic rules (regulations and legislations, the pressure from state authority), normative rules (professionalization) as well as mimetic rules (disclosure practices of other councils, and the influence of external auditor).